Prevalence of breastfeeding among indigenous peoples of the Triple Frontier: Brazil, Argentina and Paraguay - Bianca da Silva Alcantara Pereira; Adriana Zilly; Juliana Cristina dos Santos Monteiro; Nayara Gonçalves Barbosa; Flávia Azevedo Gomes-Sponholz (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to verify the prevalence of breastfeeding and the children's nutritional status of indigenous origin up to two years of age in the triple frontier region: Brazil, Argentina and Paraguay. Methods: data from the Sistema de Vigilância Nutricional e Alimentar Indígena (Indigenous Food and Nutrition Surveillance System) were analyzed, being a cross-sectional and descriptive study. The survey was carried out in 2018, with data referring to 2017. Registrations of indigenous children of both sexes,aged zero to two years old were included. Data were extracted from the indigenous children's follow-up map. The prevalence of breastfeeding and complementary feeding was evaluated. Results: the prevalence of exclusive breastfeeding in children under six months of age was 93.4% and complementary breastfeeding was 6.5%. The prevalence of complementary breastfeeding after six months was 71.6% and exclusive breastfeeding after six months was 28.3%. Regarding social benefits, 30.3% of the families accumulated two types of social benefits. Conclusions: the prevalence of exclusive breastfeeding was high and surpassed the national prevalence in the first semester of life, there was no early weaning.